ДОСЛІДЖЕННЯ АВАРІЙНИХ РЕЖИМІВ КАСКАДНИХ ТРАНСФОРМАТОРІВ СТРУМУ ЗА РОЗМИКАННЯ ЇХНІХ ВТОРИННИХ КІЛ - Журахівський, А.В.; Кенс, Ю.А.; Равлик, О.М.; Ференсович, Р.Я. (Інститут електродинаміки НАН України, Київ, 2018)
The article presents a calculation scheme of a two-stage cascade current transformer for a computer simulation its operation modes after disconnection under load secondary circuits, which was created by the authors. The analysis of the results of computer calculation steady-state and transient modes of investigated cascade current transformer type TOM-765 after opening its secondary windings considering active power losses in the magnetic cores of stages is carried out. The obtained calculation oscillograms describe the character of the processes in the respective stages of the cascade current transformer for the mode of open its secondary circuits. References 13, tables 2, figures 5.